(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess patient satisfaction with postoperative care and analyze associated factors among inpatients at Transport Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 210 postoperative inpatients at Transport Hospital between January and December 2024. Data were collected using a standardized patient satisfaction questionnaire and analyzed with SPSS, applying descriptive statistics and Chi-square tests to identify significant associations. Results: Overall satisfaction rate was 86.7%. Significant factors associated with satisfaction included length of hospital stay (p<0.05), nutritional and baseline health status (p<0.05), and patient–healthcare staff interaction (p<0.01). Patients with shorter hospital stays and better health conditions reported higher satisfaction levels. Conclusion: Patient satisfaction with postoperative care at Transport Hospital was relatively high. However, aspects such as communication and hospital facilities still require improvement. The findings provide essential evidence for developing strategies to enhance the quality of comprehensive patient care.